2015
DOI: 10.1080/13588265.2015.1060731
|View full text |Cite
|
Sign up to set email alerts
|

Head boundary conditions in pedestrian crashes with passenger cars: six-degrees-of-freedom post-mortem human subject responses

Abstract: In pedestrian-vehicle crashes, head injuries cause death and long-term disability. Thus, understanding the head kinematics is vital. Head rotation data are scarce, and the influence of individual anthropometry, upper body and arm kinematics on head kinematics is poorly understood. This paper investigates the influence of anthropometry, upper body and arm kinematics on head linear and angular kinematics, providing novel six-degrees-of-freedom data from pedestrian-vehicle-crash experiments. Five similarly positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Regarding body injured regions by pedestrians, comparatively consistent findings have been reported in past studies —research has suggested that head/lower/upper extremities injuries are the most common injury regions. Head injuries tend to be more life‐threatening, while lower/upper extremities are likely to lead to long‐term disability .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding body injured regions by pedestrians, comparatively consistent findings have been reported in past studies —research has suggested that head/lower/upper extremities injuries are the most common injury regions. Head injuries tend to be more life‐threatening, while lower/upper extremities are likely to lead to long‐term disability .…”
Section: Introductionmentioning
confidence: 99%
“…The Finite Element Method (FEM) addresses the reason for the logical plan of the issue (10). The information about underlying reaction to crashes for different method for transport can be definitive in various applications (11). PC-Crash incautious model re-enactments results are thought of effective signs of the genuine kinematics (12).…”
Section: Literature Surveymentioning
confidence: 99%
“…Cadaver tests provide model validation data and have the potential to greatly strengthen our understanding of pedestrian ground contact. However, previous tests have mainly focused on vehicle contact, with limited reference to ground contact (Kerrigan et al, 2007;Masson et al, 2007;Paas et al, 2015;Subit et al, 2008) or else crash test dummies were used (Hamacher et al, 2011;Taneda et al, 1973). In early work, (Cavallero et al, 1983) concluded that head-ground contact location and speed could not be predicted from vehicle shape.…”
Section: Introductionmentioning
confidence: 99%
“…However, tests were performed only at 32 km/h, vehicle shapes have changed substantially and no ground contact kinematics or injuries were reported. More recently, cadaver studies performed in the US and France have used a range of vehicle shapes and pedestrian sizes (Kerrigan et al, 2007;Paas et al, 2015;Subit et al, 2008), but ground contact kinematics/injuries were not evaluated. In fact, the sequence of pedestrian motion following head contact on vehicle has received little attention and is poorly described.…”
Section: Introductionmentioning
confidence: 99%